The ACTUALIZATION OF CHARACTER ISLAMIC VALUES IN HIZBUL WATHAN EXTRACURRICULAR SMP MUHAMMADIYAH 8 WONOGIRI - azra azra; Hafidz (Edukasia, 2024)
The rapid development of the world emphasizes the importance of education as a strategic element in shaping human character. The strength of a nation's character through education is fundamental, particularly in the context of Islamic values for students in Indonesia. Schools, as formal educational institutions, play a significant role in shaping the character of students, especially during transitional periods such as the transition from junior high school to senior high school. In this context, the Hizbul Wathan extracurricular activity at Muhammadiyah 8 Junior High School Wonogiri is considered a crucial platform for actualizing Islamic character values. The cultivation of Islamic values character is carried out through the four pillars of character education development, including extracurricular activities. Generally, extracurricular activities are seen as supportive means in learning, and at Muhammadiyah 8 Junior High School Wonogiri, Hizbul Wathan is a mandatory extracurricular activity that shapes students' characters with Islamic values. This research aims to understand the process of actualizing Islamic values character in the Hizbul Wathan extracurricular activity and identify supporting and inhibiting factors. The research approach used is descriptive qualitative with a case study design. The data sources used in this study are primary and secondary data. Primary data sources in this study were obtained through direct observation of the research object. Meanwhile, secondary data sources in this study were obtained from documents such as school profiles, books, journals, and theses related to the actualization of Islamic values character in the Hizbul Wathan extracurricular activity. In collecting data, the researcher took several steps to gather valid data, namely observation, interviews, and documentary studies. The triangulation technique was used to check the validity of the data. The results of this research are expected to provide a deeper insight into concrete efforts to instill Islamic character through extracurricular activities, especially during the transitional period for students. It also serves as a foundation for increasing awareness and participation among students, parents, and the community in supporting Islamic character education in schools.